Tradisi Sunat Sifon dan Struktur Sosial Etnis Dawan - Hendra Hendra; Raemon Raemon; Danial Danial; Intan Kumbayoni; Hasniah Hasniah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
This study examines the tradition of sifon circumcision practiced by the Dawan ethnic group in East Nusa Tenggara within their social and cultural context. This research aims to understand how the sifon practice functions as a social mechanism that strengthens community cohesion and identity, as well as the accompanying health implications. This study employs a qualitative approach with thematic analysis methods supported by literature reviews and interviews. Bronislaw Malinowski's structural functionalism theory is used to analyze the social functions of this ritual. The findings indicate that sifon circumcision is not only an essential rite of passage within the social structure of the Dawan ethnic group, but it also serves as a means to maintain social and psychological balance within the community. The Dawan ethnic group continues to maintain the sifon practice as a vital part of their cultural identity, despite challenges posed by modernization and increased awareness of health risks.